Radiographic and clinical outcomes in adolescent idiopathic scoliosis corrective fusion surgery: a one year follow up - Blankson, Benjamin (Division of General Surgery, 2024)
Introduction Adolescent idiopathic scoliosis (AIS) is a complex three-dimensional deformity of the spine, characterized by a Cobb angle of at least 10 degrees. The goal of surgery is not only to prevent progression, but restoration of sagittal and coronal balance, protection of cardiopulmonary function and improvement of cosmesis. In this study, we reviewed the impact of deformity correction surgery in terms of radiology and patient reported outcomes. Method Data extracted from a prospectively maintained database (2003 – 2022) was retrospectively analysed for pre- and post-operative patient reported outcome measures, captured using the Scoliosis Research society-22 (SRS-22) questionnaire, as well as radiological parameters. Forty-four patients with AIS were identified with pre- and post-operative PROMs. The average age at surgery was 15yrs with 84% female. 38% had a Lenke 1 curve and 3 patients had Lenke 6 curves. 73% had posterior approach surgery. Results There was a total improvement in SRS-22 scores by 7.8% with 75% achieving MCID. Patients reported significant satisfaction with treatment 4.8/5 and improvement in self-image with a change of 1.1 (p0.05). Overall, proximal thoracic (PT) curves improved from 240 to 110 (p<0.05).